POLITICAL BEHAVIOR AND MINTZBERG’S POLITICAL GAMES: EXAMPLE OF ORGANIZED CRIMINAL INSTITUTIONS WITH GODFATHER FILM ANALYSIS - Metin Karademir; Asli Cillioglu Karademir (European Scientific Journal, ESJ, 2015)
Social facts cannot be observed directly as in the case of the facts of natural sciences. At this point, art enables understanding and interpretation of human relations through cinema, theater and literature. On the other hand, the creators of works of art reflect social relations through their own perspectives and, in this respect, subjectivity is in question; however this is acceptable to a certain extent as, after all, they are part of social facts as a member of the society and, at least, they have the potential of reflecting social facts. From this point of view, in this study, the political behaviors and political games in organizations, as stated by Mintzberg (1985), will be described by exemplifying, through analysis of a film.